The Relationship between Marital Satisfaction and Marital Justice through the Mediating Role of Anxiety in Married Students - Bahadori, Bahareh; Asgari, Parviz; Naderi, Farah (Advances in Nursing & Midwifery, 2025)
Abstract Introduction: Marital satisfaction and justice are crucial components of a healthy marriage, yet little is known about the psychological factors that may influence this relationship. Understanding the role of anxiety in the relationship between marital satisfaction and justice can provide valuable insights into the dynamics of marital relationships and inform interventions to improve marital well-being. This research aims to investigate the direct and indirect effects of marital justice on marital satisfaction, with anxiety as a potential mediator, among married students. Methods: This descriptive study employed structural equation modeling (SEM). A sample of 356 married students from Azad University, Ahvaz, Iran, was selected in 2023 using stratified random sampling. Research instruments included the Marital Satisfaction Scale, Marital Justice Scale, and State-Trait Anxiety Inventory. Data were analyzed using SEM with SPSS-26 and Amos-26 statistical software. Results: The results indicated that marital justice had a significant negative correlation with anxiety (β=-0.21, P=0.002). Additionally, both marital justice (β=0.25) and anxiety (β=-0.19) were significantly correlated with marital satisfaction (P<0.01). The results also indicated an indirect relationship between marital justice and marital satisfaction through the mediation of anxiety (P=0.011). Conclusions: The study found a strong negative correlation between marital justice and anxiety, indicating that increased marital fairness leads to decreased anxiety. Additionally, the research confirmed that marital justice positively impacts marital satisfaction both directly and indirectly by reducing anxiety levels.